MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERINTEGRASI LESSON STUDY UNTUK MENINGKATKAN SIKAP ILMIAH SISWA SMA - Tenggarudin Tenggarudin; Kasman Arifin (Gema Pendidikan, 2021)
This study aims at describing the tendency of scientific attitudes of state high school students in Kendari City after going through the integrated problem-based learning (PBL) lesson study. The research subjects were class X students who came from three public high schools in Kendari. The learning activities in each class were carried out in three meetings (using three lesson plans) which were designed using a pre-experimental design One Group Pretest-Posttest Design. The results showed that the implementation of the integrated lesson study PBL learning model in each school tended to improve students' scientific attitudes. The obstacles faced by students in learning were mainly related to the limited time available each time they met face to face, and the internet facilities in schools less guarantee to find the information needed by students.